2017
DOI: 10.1007/s11239-017-1493-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a predictive model for 6 month survival in patients with venous thromboembolism and solid malignancy requiring IVC filter placement

Abstract: Purpose Our purpose was to develop a predictive model for short-term survival (i.e. less than 6 months) following inferior vena cava filter placement in patients with venous thromboembolism (VTE) and solid malignancy. Materials and Methods Clinical and laboratory parameters were retrospectively reviewed for patients with solid malignancy who received a filter between January 2009 and December 2011 at a tertiary care cancer center. Multivariate Cox proportional hazards modeling was used to assess variables as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For example, Huang et al identified serum albumin, tumor stage and history of surgery within 30 days as independent risk variables for 6-month survival in patients with malignancy combined with VTE who underwent inferior vena cava filter placement. 11 The prediction model had an AUC of 0.815. However, the authors did not provide further parameters or calibration plots for this model, and neither internal nor external validation was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Huang et al identified serum albumin, tumor stage and history of surgery within 30 days as independent risk variables for 6-month survival in patients with malignancy combined with VTE who underwent inferior vena cava filter placement. 11 The prediction model had an AUC of 0.815. However, the authors did not provide further parameters or calibration plots for this model, and neither internal nor external validation was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies in this area have focused on the prediction of VTE risk in specific populations. [7][8][9][10][11]35 For example, McCurdy et al identified the incidence and risk variables for VTE in 2161 patients with inflammatory bowel disease (IBD) after discharge and developed a prediction model to assess VTE risk. 35 The final model included age >45 years, multiple admissions, intensive care unit admissions, length of admissions >7 days and central venous catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation